Biological activities of unique isoflavones prepared from Apios americana Medik. Issue 4 (2nd April 2016) - Kaneta, Haruna; Koda, Mina; Saito, Shun; Imoto, Masaya; Kawada, Manabu; Yamazaki, Yoko; Momose, Isao; Shindo, Kazuoshi
Abstract: Four unique isoflavone aglycones (barpisoflavone A (1 ), 2′-hydroxygenistein (2 ), 5-methylgenistein (3 ), and gerontoisoflavone A (4 )) whose structures were related to genistein were prepared from the tuber of Apios americana Medik. We examined the estrogen receptor and androgen receptor binding activities, estrogen agonistic activities, antioxidant activities, and α-glucosidase inhibitory activities of 1–4 . The results obtained showed that 2 possessed potent and 1, 3, and 4 possessed moderate estrogen partial agonistic activities, 1 and 2 possessed moderate antioxidant activities, and 2 and 3 possessed moderate α-glucosidase inhibitory activities. Graphical abstract: : Four unique isoflavone aglycones (barpisoflavone A (1 ), 2′-hydroxygenistein (2 ), 5-methylgenistein (3 ), and gerontoisoflavone A (4 )) were prepared from the tuber of Apios americana Medik, and tested their biological activities.